2008
DOI: 10.2175/193864708788733332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Electron Donors in Anoxic Moving Bed Biofilm Reactors (MBBRs) Configured for Post-Denitrification

Abstract: The effectiveness of four different electron donors, specifically methanol, ethanol, glycerol, and sulfide, was evaluated in post-denitrifying bench-scale moving bed biofilm reactors (MBBRs). With increased concern for wastewater treatment plants to meet lower effluent nitrogen levels, alternate substrates could promote quicker startup/acclimation times and higher denitrification rates than methanol, which is most commonly used. While application of alternative substrates in suspended growth processes has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…In a bench-scale study with denitrifying, moving bed biofilm reactors, biomass growth was observed to be thicker and heavier with glycerol as the electron donor compared with methanol or sulfide. 38 This study also reported that reactor operation with glycerol was associated with higher levels of effluent total suspended solids and greater plugging of media void spaces. 38 Their estimate of the observed biomass yield with a glycerol-based electron donor (0.5 g COD biomass g −1 COD substrate [based on average effluent volatile suspended solids data]) is close to the estimated yield with the glycerol product tested in the present study (0.54 g COD biomass g −1 COD substrate , Table 2).…”
Section: Biomass Yield With the Glycerol-based Electron Donormentioning
confidence: 70%
See 1 more Smart Citation
“…In a bench-scale study with denitrifying, moving bed biofilm reactors, biomass growth was observed to be thicker and heavier with glycerol as the electron donor compared with methanol or sulfide. 38 This study also reported that reactor operation with glycerol was associated with higher levels of effluent total suspended solids and greater plugging of media void spaces. 38 Their estimate of the observed biomass yield with a glycerol-based electron donor (0.5 g COD biomass g −1 COD substrate [based on average effluent volatile suspended solids data]) is close to the estimated yield with the glycerol product tested in the present study (0.54 g COD biomass g −1 COD substrate , Table 2).…”
Section: Biomass Yield With the Glycerol-based Electron Donormentioning
confidence: 70%
“…38 This study also reported that reactor operation with glycerol was associated with higher levels of effluent total suspended solids and greater plugging of media void spaces. 38 Their estimate of the observed biomass yield with a glycerol-based electron donor (0.5 g COD biomass g −1 COD substrate [based on average effluent volatile suspended solids data]) is close to the estimated yield with the glycerol product tested in the present study (0.54 g COD biomass g −1 COD substrate , Table 2). Similarly, in a study with bench-scale, denitrifying sequencing batch reactors, the biomass yield increased over time as biomass grew on glycerol or a glycerol by-product from biodiesel fuel production.…”
Section: Biomass Yield With the Glycerol-based Electron Donormentioning
confidence: 70%